Ukraine first review of nonobservance and applicability of performance criteria - Ostrovka, Victor (My University, 2014)
The authorities have implemented policies broadly as agreed, but significant pressures have emerged.
Keywords: economic crisis; performance criteria; економічна криза; критерії якості роботи; экономический кризис; критерий производительности